Sistem Informasi Laporan Laba Rugi Pada UD. Kopi Ayam Ras Jambi - Nadia Mutiarani Arumdi Putri; Fortia magfira (LP2M Politeknik Jambi, 2021)
This study discusses the problems that occur in UD. Kopi Ayam Ras Jambi which is related to accounting records through the calculation of the income statement still uses the manual method that has not used a computerized system that is in accordance with accounting standards. From this, this situation makes it difficult for management to calculate the income statement every month. The purpose of this study is to create an Income Statement System using the single-step method, which is expected to assist management in calculating the company's profit and loss for each period. The profit and loss statement using this single step can make it easier for management to calculate the income, costs, and profit and loss generated each period. So that the management of UD. Kopi Ayam Ras Jambi can find out in real terms the company's profit and loss for each accounting period. The results of this system are expected to have an impact on efficiency and effectiveness in UD operations. Kopi Ayam Ras Jambi gets an accurate profit and loss report through maximum results.